Circulating biologic markers of endothelial dysfunction in cerebral small vessel disease: A review. Issue 1 (January 2016) - Poggesi, Anna; Pasi, Marco; Pescini, Francesca; Pantoni, Leonardo; Inzitari, Domenico
The term cerebral small vessel disease (SVD) refers to a group of pathologic processes with various etiologies that affect small arteries, arterioles, venules, and capillaries of the brain. Magnetic resonance imaging (MRI) correlates of SVD are lacunes, recent small subcortical infarcts, white-matter hyperintensities, enlarged perivascular spaces, microbleeds, and brain atrophy. Endothelial dysfunction is thought to have a role in the mechanisms leading to SVD-related brain changes, and the study of endothelial dysfunction has been proposed as an important step for a better comprehension of cerebral SVD. Among available methods to assess endothelial function in vivo, measurement of molecules of endothelial origin in peripheral blood is currently receiving selective attention. These molecules include products of endothelial cells that change when the endothelium is activated, as well as molecules that reflect endothelial damage and repair. This review examines the main molecular factors involved in both endothelial function and dysfunction, and the evidence linking endothelial dysfunction with cerebral SVD, and gives an overview of clinical studies that have investigated the possible association between endothelial circulating biomarkers and SVD-related brain changes.